2012
DOI: 10.1007/s00439-012-1253-4
|View full text |Cite
|
Sign up to set email alerts
|

A non-synonymous SNP in the NOS2 associated with septic shock in patients with sepsis in Chinese populations

Abstract: Sepsis represents a systemic inflammatory response to infection and its sequelae include severe sepsis, septic shock, multiple organ dysfunction syndrome (MODS) and death. Studies in mice and humans indicate that the inducible nitric oxide synthase (iNOS, NOS2) plays an important role in the development of sepsis and its sequelae. It was reported that several single nucleotide polymorphisms (SNPs) within NOS2 could influence the production or activity of NOS2. In this study, we assessed whether SNPs within NOS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 37 publications
1
13
0
Order By: Relevance
“…iNOS mutant mice have a blunted hypotensive response to sepsis [14]. Recently, a non-synonymous SNP in the iNOS gene has been shown to be associated with increased susceptibility to septic shock in Chinese populations [15].…”
Section: Introductionmentioning
confidence: 99%
“…iNOS mutant mice have a blunted hypotensive response to sepsis [14]. Recently, a non-synonymous SNP in the iNOS gene has been shown to be associated with increased susceptibility to septic shock in Chinese populations [15].…”
Section: Introductionmentioning
confidence: 99%
“…As suggested by Wang et al, 2013 [28] besides the SNPs investigated here, we cannot exclude the possibility of the presence of other functional polymorphisms in linkage disequilibrium (LD) with an investigated SNP being responsible for the genotype-dependent differences in iNOS activity. Further studies are needed to identify polymorphisms in this region and clarify which polymorphism(s) may possess the functional consequence(s) for the genotype-dependent differences in iNOS activity (e.g., NO levels), and provide mechanistic plausibility for the observed association between NOS2 and susceptibility to CP.…”
Section: Discussionmentioning
confidence: 71%
“…Both −1026(A>C) and +2087(A>G) single nucleotide polymorphisms (SNPs) in the NOS2 gene are potentially functional [12,18,23,28,29] and clinically relevant, as they are associated with hypertensive disorders [29,30,31,32], migraine with aura [26], and malignant neoplasias [33,34]. …”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have indicated that iNOS plays an important role in the origin of hypotension in septic shock. The A-allele carriage has been associated with increased susceptibility to septic shock [ 29 ]. Our finding indicated that the rare A-allele carriers ( i .…”
Section: Discussionmentioning
confidence: 99%